2003
DOI: 10.1177/004051750307301012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fiber Arrangement on the Mechanical Properties of Thermally Bonded Nonwoven Fabrics

Abstract: Anisotropy is important to the structure and application of nonwoven fabrics. The arrange ment of the fibers and their orientation distribution are related to the mechanical structure of the web. In this study, we used a doffer of the roller card accompanied by a random roller to produce nonwoven fabrics. Partial random fiber arrangement is obtained by transferring the fibers on the rollers. As a result, the ratios of tensile and tearing strengths of the random web are below 3.0 and above 0.5, respectively. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…The method presented here can be used for the fibrous background of the nonwoven located between the bonding points. This fibrous background is constituted of fibers whose orientation plays a major role in the mechanical properties of the surface and more particularly is directly linked to its tensile properties as mentioned for instance by Adanur et al [5], Lin et al [6] or Backer et al [7]. In this study we use images in degree of polarization.…”
Section: Characterization Of the Texture At Microscopical Scalementioning
confidence: 99%
See 1 more Smart Citation
“…The method presented here can be used for the fibrous background of the nonwoven located between the bonding points. This fibrous background is constituted of fibers whose orientation plays a major role in the mechanical properties of the surface and more particularly is directly linked to its tensile properties as mentioned for instance by Adanur et al [5], Lin et al [6] or Backer et al [7]. In this study we use images in degree of polarization.…”
Section: Characterization Of the Texture At Microscopical Scalementioning
confidence: 99%
“…They depend on elements at two scales of the surface: bonding points, i.e. macroscopic scale, and fiber orientation within the fibrous entanglement [5][6][7], i.e. microscopic scale.…”
Section: Introductionmentioning
confidence: 99%
“…Nonwoven is a web of directionally or randomly oriented fibers bonded by a certain process. There are lots of nonwoven production processes and products that have been developed . Different types of fibers are used in nonwoven production.…”
Section: Introductionmentioning
confidence: 99%
“…Genis8 established a relation between the fiber diameter, fabric thickness and the air permeability and a relation between the fiber diameter, fabric thickness, volume density and the sound absorption coefficient of melt blown nonwoven fabrics by multiple regression analysis of the experimental data. Lin et al9 investigated the effect of fiber arrangement on the mechanical properties of thermal bonded nonwoven fabrics and showed that the anisotropy of the mechanical properties of nonwoven fabrics could be improved by arranging the fibers at random. Rong and Bhat10 used differential scanning calorimetry to analyze the binder fiber distribution of thermal bonded nonwoven fabrics and investigated the relationship of binder fiber distribution and the tensile strength of nonwovens.…”
Section: Introductionmentioning
confidence: 99%